Art and immortality in the ancient near east - Ataç, Mehmet-Ali 1972- (Cambridge, UK New York, NY Cambridge University Press, 2018)
Archaeological Discovery and Architectural SettingThe Mari Painting in the Context of the Art of the Ancient Near East; The Affinity between Mari and Assyria; Conceptions of Renewal in the Mari Painting; The Flood Myth in the Old Babylonian Period; Previous Interpretations; Alternative Views; A Critical Position; Two The Iconographic Analysis of the Mari Painting; The Ring and Rod: Beyond Legitimacy; The Builder King; Gradation and Framing; The Flowing Vase: Beyond Fertility; Aquatic Endlessness; Ishtar and Ea; An Aquatic Doorway; The Central Panel: Beyond a Rectangular Frame; Heaven in Earth.
Cover; Half-title; Title page; Copyright information; Epigraph; Table of contents; List of Illustrastions; Acknowledgments; List of abbreviations; Introduction; Toward a Metaphysics of the Art of the Ancient Near East; The Corpus of Images; Questions of Text and Image; Tammuz and Gilgamesh; A Supra-Textual Language; Conceptual Bases; Egypt and Mesopotamia; Conceptions of Sacral Time and Eschatology; Defining Apocalyptic; Out of Time, Out of History; Artistic Production and "Regal Art"; The Royal Destiny; Art and the Apocalyptic; One The "Investiture" Painting from Mari.
Discussions of apocalyptic thought and its sources in the ancient Near East, particularly Mesopotamia, have a long scholarly history, with a renewed interest and focus in the recent decades. Outside Assyriological scholarship as well, studies of the apocalyptic give significant credit to the ancient Near East, especially Babylonia and Iran, as potential sources for the manifestations of this phenomenon in the Hellenistic period. The emphasis on kingship and empire in apocalyptic modes of thinking warrants special attention paid to the regal art of ancient Mesopotamia and adjacent areas in its potential to express the relevant notions. In this book, Mehmet-Ali Ataç demonstrates the importance of visual evidence as a source for apocalyptic thought. Focusing on the so-called investiture painting from Mari, he relates it to parallel evidence from the visual traditions of the Assyrian Empire, ancient Egypt, and Hittite Anatolia
Postscript: Why the Apocalyptic Would Have Been EsotericSix The "Royal Destiny":; From Ashurnasirpal to Ashurbanipal; Description and Historical Framework; Previous Interpretations and the Present Approach; Paradisiac Implications; The "Garden Scene" and its Intercultural Connections; "The Charms of Tyranny"; The Assyrian Queen Wearing the Mural Crown; The Celestial City; The Garden as a Transitional Extreme; A Vergilian Model; Ishtar and "Holy War"; Closure to the "Garden Scene"; Epilogue; Notes; Introduction; 1 The "Investiture" Painting From Mari.
Primordial Chaos as Source of Periodic Destruction and RenewalSerpents, Streams, and Endless Time; Neo-Sumerian Roots; An Anatolian Ouroboros.?; Five Implications of Sacral Time and Eschatology; Temporal Cyclicality in Ancient Mesopotamia; An Apocalyptic Perspective; Defying Cyclicality through Ascent; The Hittite Double Winged Disk; Hittite Visual Formulations of Ascent; Mountain and Water; To Die is to Become a God; Egyptian Roots; Conceptions of Temporal and Astral Eternity; Nothing Babylonian; Conceptions of Apocalyptic Eschatology; Closure to the Mari Painting.
The Mythical Quadrupeds: Beyond the ApotropaicThe Blue Bird in Flight: The "Phoenix"?; Ascent to Heaven; Coloristic Symbolism; Stairway to Heaven; Three The Flood Myth as Paradigm; A Note on Method; The Ideal Enclosure and the Ideal Garden; The Ideal Temple; Numerological Symbolism; A New Cosmic Order; Flood Vision; Defining Paradeigma; The Mari Painting and the Assyrian "Sacred Tree"; Postscript on Shamanic Lore in the Art of Ancient Mesopotamia; Four The Semantics of the Frame of Running Spirals; Running Spirals as Symbolic Form; The Ouroboric Serpent.
Includes bibliographical references and index
Title from publisher's bibliographic system (viewed on 26 Feb 2018)
Keywords: Time and art; Holy, The, in art; Apocalyptic art; Art, Ancient -- Middle East -- Themes, motives; ART ; History ; General; Art, Ancient ; Themes, motives; Middle East